Ulnar Neuropathy at the Elbow in Chronic Alcohol-Dependent Subjects. Issue 1 (September 2016) - Zambelis, T.; Kanelli, S.; Tzavellas, E.; Paparrigopoulos, T.; Karandreas, N.
Abstract: Objectives: To evaluate the occurrence of Ulnar neuropathy at the elbow (UNE) among alcohol dependent subjects. Method: The study sample comprised 99 consecutive alcohol dependent subjects treated for detoxification voluntarily in the specialized unit of the Athens University Psychiatric Clinic in an inpatient basis. Results: UNE was found in 51 subjects (51.5%): in 40.4% on the right side, in 44.6% on the left and in 20.1% on both. Polyneuropathy was diagnosed in 41.4% of the total sample. Statistical analysis showed UNE significantly associated with age of the subjects, age at alcohol dependence onset and duration of alcohol dependence. Was more frequent in men and the probability of UNE was lower in obese subjects. Conclusions: UNE is frequent among alcohol dependent subjects and they must be instructed to avoid abnormal postures and to protect their elbow while working with the elbows flexed and resting on a hard object.